Intermolecular Hybridization Governs Molecular Electrical Doping - Salzmann, Ingo; Heimel, Georg; Duhm, Steffen; Oehzelt, Martin; Pingel, Patrick; George, Benjamin M.; Schnegg, Alexander; Lips, Klaus; Blum, Ralf-Peter; Vollmer, Antje; Koch, Norbert (Physical review letters, 2012)
Current models for molecular electrical doping of organic semiconductors are found to be at odds with other well-established concepts in that field, like polaron formation. Addressing these inconsistencies for prototypical systems, we present experimental and theoretical evidence for intermolecular hybridization of organic semiconductor and dopant frontier molecular orbitals. Common doping-related observations are attributed to this phenomenon, and controlling the degree of hybridization emerges as a strategy for overcoming the present limitations in the yield of doping-induced charge carriers.